Analisis Implementasi Penanganan Prasarana Dan Sarana Umum Di Kelurahan Grogol Tahun 2022 - Yurisman Star; Krishantoro Krishantoro; Sribima Raja Sakti (Institut Ilmu Sosial dan Manajemen STIAMI, 2023)
The background of the problems was related to the performance carried out by PPSU (Public Infrastructure and Facilities Management) employees. There were still many external and internal problems in managing the Management of Public Infrastructure and Facilities. At the external level, one of the problems faced by PPSU employees was the need for more public awareness regarding environmental cleanliness, which often added to the work done by PPSU employees. This study aimed to identify and analyze the implementation of Public Infrastructure and Facilities Management in Grogol Urban Village in 2022, to find out and analyze the inhibiting factors in implementing the Management of Public Infrastructure and Facilities in Grogol Urban Village in 2022, and to know and analyze the efforts made to overcome obstacles to the implementation of Public Infrastructure and Facilities Management in Grogol Urban Village in 2022. This research employed a qualitative method with a descriptive approach. In-depth interviews were conducted with seven informants. Source triangulation was used to check the validity of the data. The study results showed that implementing of Public Infrastructure and Facilities Management in the Grogol Urban Village in 2022 was quite good. However, in its implementation, it was not enough to say it was good enough because there were several SOPs that some PPSU employees have not understood. Therefore, PPSU officers must improve their skills and expertise to manage the Public Infrastructure and Facilities Management related to the work demands.